Metabolic syndrome and its components are associated with lengths of stay in a psychiatric hospital: Results from a Swiss psychiatric cohort and first-episode psychosis patients - Nermine Laaboub; Setareh Ranjbar; Séverine Crettol; Nicolas Ansermot; Frederik Vandenberghe; Carole Grandjean; Marianna Piras; Julien Elowe; Martin Preisig; Armin Von Gunten; Philippe Conus; Chin Bin Eap (European Psychiatry)
Abstract